EVALUATION OF THE FREQUENCY OF FOOD INTAKE AND THE MAINTENANCE OF THE EFFECT OF GLUTAMINE SUPPLEMENTATION ON THE ATTENUATION OF SYMPTOMS OF MODERATE ASTHMA IN CHILDREN, POST WASH OUT - Carlyle Pietrobom; Michele Honicky; Mariana Saciloto; Mariana Abe Vicente Cavagnari; João Paulo Zattar; Claudia Nodari; Angelica Rocha de Freitas Melhem (Demetra, 2019)
The objective of the study was to compare the frequency of food intake of children with moderate asthma with that of children without respiratory diseases and to evaluate the maintenance of the effect of the immunomodulator glutamine on the attenuation of asthma symptoms after the washout period. Longitudinal intervention study with children from 2 to 7 years of age. The study consisted of three groups: glutamine case group, control group with asthma and control group without respiratory disease, with 15 children each. The clinical evaluation was performed by means of the ISAAC Questionnaire – Asthma Module before the beginning of the supplementation and in monthly visits during the 4 months of the study, and repeated after the 6-month washout period. Children in the control group without respiratory disease were evaluated (food intake frequency) at a single point in time. The food intake was assessed by means of the adapted FFQ. There was a significant decrease in the ISAAC score in the glutamine group after 4 months of supplementation [8.0 (1.46) x 4.0 (1.96), p<0.001], as well as in the control group with asthma [8.67 (1.79) x 5.93 (2.28), p<0.001]. After the washout period there was a significant increase in the score and return of asthma symptoms in the glutamine case group [4.0 (1.96) x 7.27 (2.02), p<0.001]. The food intake was similar among children with asthma and without asthma, characterized by daily consumption of milk and low consumption of vegetables, fruits and meat. The beneficial effect of glutamine was not maintained after the washout period.